Antecedents of well-being for artisan entrepreneurship: a first exploratory study. (24th August 2020) - Loarne-Lemaire, Séverine Le; Partouche-Sebban, Judith; Razgallah, Myriam; Maalaoui, Adnane
Studies examining the well-being of artisan entrepreneurs have not been widely developed. Some scholars have studied the entrepreneurial phenomena in the field of handicraft in general, focusing on the motivations, goals and perceptions of success of artisan entrepreneurs. However, studies regarding artisan entrepreneurs and, specifically, their quality of life and well-being have not been sufficiently discussed in this entrepreneurship literature. For that reason, this paper explores the well-being of artisan entrepreneurs and seeks to identify the antecedents of this well-being. We conducted an exploratory qualitative study through which we highlighted some important characteristics of artisan entrepreneurs' well-being, such as passion, personality, creativity, culture and heritage. On the basis of these findings, we propose and discuss a first model of the antecedents of well-being for artisan entrepreneurs.